Supratentorial clear cell ependymomas with branching capillaries demonstrate characteristic clinicopathological features and pathological activation of nuclear factor-kappaB signaling. Issue 7 (15th March 2016) - Figarella-Branger, Dominique; Lechapt-Zalcman, Emmanuèle; Tabouret, Emeline; Jünger, Stephanie; de Paula, André Maues; Bouvier, Corinne; Colin, Carole; Jouvet, Anne; Forest, Fabien; Andreiuolo, Felipe; Quintin-Roue, Isabelle; Machet, Marie-Christine; et al.
Abstract: Background: Clear cell ependymoma is one of the 4 main histological subtypes of ependymomas defined by the World Health Organization (WHO) classification of tumors of the CNS. DNA methylation profiling can distinguish 4 subgroups of intracranial ependymomas, including supratentorial (ST) ependymomas with Yes-associated protein 1 fusion (YAP1), ST ependymomas with fusion of v-rel avian reticuloendotheliosis viral oncogene homolog A (RELA), posterior fossa ependymomas with balanced genome, and posterior fossa ependymomas with chromosomal instability. In addition, trisomy 19 is a genomic hallmark of ependymomas with rich branching capillaries. However, the relation of histological and molecular subtypes is unclear. Methods: Here, we report a series of 20 ependymomas histologically defined by clear cells and branching capillaries. Results: We observed a strong male predominance. Median age at surgery was 10.4 years (range, 0.8–68.4). All cases were ST, cortical, contrast enhancing, and most often frontal, cystic, and calcified. All tumors qualified as WHO grade III. Some of them exhibited neuronal differentiation. Trisomy 19 was recorded in 13 cases. All samples strongly accumulated p65RelA protein within nuclei, indicating pathological activation of the nuclear factor-kappaB pathway. We identified causative C11ORF95-RELA fusion in almost all cases. Median progression-free survival and overall survival were 11.4 years (95% CI: 5.1–17.8) and not reached, respectively. Conclusion: ST clear cell ependymomas with branching capillaries display characteristic clinicopathological features and are associated with pathological activation of nuclear factor-kappaB signaling, which may indicate a potential novel target for therapy in these patients.